Penyuluhan Pembuatan Pupuk Organik Cair Ramah Lingkungan dari Limbah Kulit Pisang di Desa Banyumas Kabupaten Bengkulu Utara Provinsi Bengkulu - Wulandari, Sri; Yuwita, Fitri; Koto, Hidayat (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
The abundant banana peel waste in Banyumas Village, North Bengkulu Regency, has not been optimally utilized, thus potentially polluting the environment. In fact, banana peels contain important nutrients such as potassium, phosphorus, and magnesium that are beneficial for soil fertility. This community service activity aims to increase community knowledge and skills in processing banana peel waste into environmentally friendly liquid organic fertilizer (POC) as an alternative solution to increase agricultural productivity. The implementation method includes lectures, demonstrations of POC production, and pretest and posttest evaluations to measure the increase in participant understanding. The results of the activity showed a significant increase in community knowledge and skills in utilizing banana peel waste to make POC. The community service participants were also active in the activity by providing responses to questions and enthusiastically demonstrating the stages of making liquid organic fertilizer from banana peel waste. This activity is expected to raise public awareness of the importance of organic waste management and provide appropriate technological solutions that can be implemented at the household and farmer group levels.